2021
DOI: 10.21203/rs.3.rs-189491/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

FMRI Functional Connectivity Evaluation in Alzheimer’s Stages: Linear and Non-Linear Approaches

Abstract: Neuroimaging data analysis reveals the underlying interactions in the brain. It is essential, yet controversial, to choose a proper tool to manifest brain functional connectivity. In this regard, researchers have not reached a definitive conclusion between the linear and non-linear approaches, as both have pros and cons. In this study, to evaluate this concern, the functional Magnetic Resonance Imaging (fMRI) data of different stages of Alzheimer’s disease are investigated. In the linear approach, the Pearson … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…This threshold, apart from ensuring scale freeness, enables one to better differentiate among groups (refer to Supplementary material ). Other researchers using rsfMRI datasets concluded that a threshold between 0.21 and 0.4 is optimal to enable the differentiation of groups ( Aurich et al, 2015 ; Ye et al, 2015 ; Ahmadi et al, 2021 ; Ng et al, 2021 ). Graph theory measures were performed using the brain connectivity toolbox: https://sites.google.com/site/bctnet/ .…”
Section: Methodsmentioning
confidence: 99%
“…This threshold, apart from ensuring scale freeness, enables one to better differentiate among groups (refer to Supplementary material ). Other researchers using rsfMRI datasets concluded that a threshold between 0.21 and 0.4 is optimal to enable the differentiation of groups ( Aurich et al, 2015 ; Ye et al, 2015 ; Ahmadi et al, 2021 ; Ng et al, 2021 ). Graph theory measures were performed using the brain connectivity toolbox: https://sites.google.com/site/bctnet/ .…”
Section: Methodsmentioning
confidence: 99%